Implementation of Let’s Read and Wordwall Application in Improving Elementary School Students’ Reading Literacy - Desrirori, Malika; Rahayu, Novitri; Rosiana, Yurike (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2025)
This study aims to develop and implement the Let's Read and Wordwall applications as an innovation to improve the reading skills of elementary school students. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). During the analysis phase, students' literacy needs are identified by involving teachers and students as research subjects. Then, on the design and development stage, the Let's Read application is used to present various interactive stories, while Wordwall is used to create interesting quizzes and literacy games. The implementation stage includes face-to-face and online testing to assess the effectiveness of the application, while the evaluation is carried out by analyzing the results of the questionnaire distributed to students. The results of the study showed that the use of Let's Read and Wordwall significantly increased students' interest and reading ability. This study also provides recommendations for the application of applications in interactive learning in elementary schools.